SISTEM KENDALI PINTU DENGAN SENSOR SENTUH, INFRARED, DAN KIPAS MENGGUNAKAN VOICE RECOGNITION BERBASIS NODEMCU - Adisty Kamila; Mariza Wijayanti; Yuli Fitriyani (Asosiasi Dosen Muda Indonesia, 2024)
Technology is developing rapidly and home security is very important for all householders. This door control system is designed so that house residents feel safe and comfortable when entering and leaving the house. Residents can use door magnets and touch sensors to lock doors and receive information via WhatsApp to monitor when creatures enter their homes.The design of this tool system uses a Nodemcu ESP8266 microcontroller to process data collected through touch, infrared and sound sensors. This touch sensor is used to open the door or move the servo to open the door, and the door solenoid valve is used to unlock the door. The infrared sensor will then detect when someone enters your home, a buzzer will sound, and a notification will be sent via WhatsApp. The sound sensor is used to turn the fan on and off.